Managing Religion and Religious Changes in Iran: A Socio-Legal Analysis, by Sajjad Adeliyan Tous and James T. Richardson - Golyari, Mohammad-Hossein (International journal for the study of new religions, 2023)
Managing Religion and Religious Changes in Iran: A Socio-Legal Analysis, by Sajjad Adeliyan Tous and James T. Richardson. Cambridge University Press, 2024. ePDF. 80 pp. $23.00. ISBN: 9781009460095